Mass torts in the United States : strategy & practice - Ward-Reichard, Courtney E. (American Bar Association, Litigation Section, 2021)
"The American Bar Association's Mass Tort Litigation Committee is proud to present this extensive work on so many of the critical aspects of litigation in this area. This book is intended to be insightful and practical, and will serve as an excellent resource on strategies for prosecuting and defending mass tort litigation. From class certifications and use of MDLs to discovery and experts; from emerging damage theories and related defenses to the conduct of trials, appeals and the formulation of exit strategies and settlements, this work will be highly instructive. We are grateful for the tireless efforts of all those distinguished lawyers who contributed to this superb book. Arvin Maskin Weil, Gotshal & Manges, LLP Former Co-Chair, ABA Committee on Mass Tort Litigation"--